For mobilizing communication (at last) for the planet - Lahiala, Abdelfattah; de Souza Salles, Sergio; F. A. Barros, Victor (Cadernos de Educação Tecnologia e Sociedade, 2024)
Communication is the cornerstone of collective action, especially as we confront the planet’s future. Volume 17, Issue 4 of the Brazilian Journal of Education, Technology and Society (BRAJETs) presents 25 articles across three thematic sections, reinforcing the journal’s mission to advance knowledge at the nexus of communication, education, and societal change. The opening section, “For Mobilizing Communication Science for the Planet,” features nine articles from the Congrès International des Sciences de la Communication (CISC’24), exploring how communication fosters environmental awareness, drives sustainable behavior, and leverages technology to address global issues. Topics include chatbot use in crises, branding for sustainable tourism, and the link between education and strategic communication. The second section, “Novel Approaches in Education, Society, and Culture Development,” examines innovative methods to enhance pedagogy, social advancement, and resource use, with studies on game-based learning, AI in education, and machine learning for sustainability. The final section, “Cultural, Economic, and Educational Interconnections in Society,” investigates digital transformation, cultural identity, and policy-making, addressing themes like the digitization of education and intercultural communication during crises. Each article was rigorously reviewed through a double-blind process, ensuring academic rigor and practical relevance. This issue not only highlights BRAJETs’ role in bridging theory and practice but also urges readers to reflect, innovate, and act—advancing communication as a catalyst for both planetary and human flourishing. We invite you to explore these contributions and join the global effort to mobilize communication for a better future.